The Analysis of Implicature in the Presidential Election Campaign 2019 on Online Billboard Advertisement - Widyashanti Kunthara Anindita (Faculty of Language and Literature, University of Surakarta, 2018)
This study aims to describe and explain 1) The implicatures on the utterances of 2019 Presidential election campaign on online billboard advertisements (2) The types of implicatures on the utterances of 2019 Presidential election campaign on online billboard advertisements (3) The function of those implicatures. The research method in this study is a qualitative approach that uses content analysis. This is intended to trace three formulation of problems related to the conversational implicature. Data is the utterances containing implicatures and data is taken from 2019 presidential election campaign on online billboard advertisements. The results of the discussion showed that out of 11 online billboards, most speakers flouted Quality maxim as much as 6 online billboard advertisements and the speakers also flouted Quantity maxim as much as 3 online billboards advertisements. The rest, 1 online billboard advertisement includes the flouting of manner maxim and 1 online billboard advertisement includes the flouting of Relation maxim. The types of implicatures that occur are generalized implicatures and particularized implicatures. Implicature in this study has 2 functions, namely directive (asking, inviting and convincing) and commissive (promising).